The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1073/pnas.1305934110
|View full text |Cite
|
Sign up to set email alerts
|

Site-2 protease substrate specificity and coupling in trans by a PDZ-substrate adapter protein

Abstract: Site-2 proteases (S2Ps) are intramembrane metalloproteases that cleave transmembrane substrates in all domains of life. Many S2Ps, including human S2P and Mycobacterium tuberculosis Rip1, have multiple substrates in vivo, which are often transcriptional regulators. However, S2Ps will also cleave transmembrane sequences of nonsubstrate proteins, suggesting additional specificity determinants. Many S2Ps also contain a PDZ domain, the function of which is poorly understood. Here, we identify an M. tuberculosis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Though ECF sigma factors are regulated by extracytoplasmic stimuli, only some are held inactive by a cognate membrane-embedded anti-sigma factor which would be a candidate substrate for Rip1. We previously demonstrated the topology of anti-sigma factors K, L, and M as transmembrane proteins with extracytoplasmic C termini (15). To search for additional anti-sigma factors that might be candidate Rip1 substrates, we analyzed additional anti-sigma factors annotated in the M. tuberculosis genome for putative transmembrane domains and determined their topology in the mycobacterial membrane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though ECF sigma factors are regulated by extracytoplasmic stimuli, only some are held inactive by a cognate membrane-embedded anti-sigma factor which would be a candidate substrate for Rip1. We previously demonstrated the topology of anti-sigma factors K, L, and M as transmembrane proteins with extracytoplasmic C termini (15). To search for additional anti-sigma factors that might be candidate Rip1 substrates, we analyzed additional anti-sigma factors annotated in the M. tuberculosis genome for putative transmembrane domains and determined their topology in the mycobacterial membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Fusions of the C termini of RsdA and RsgA to alkaline phosphatase (PhoA) or ␤-galactosidase (␤-Gal) were constructed by ablating the termination codon of RsdA or RsgA such that the terminal amino acid (H299 for RsdA or T244 for RsgA) was fused to the coding sequence of either lacZ or phoA. Alkaline phosphatase and ␤-galactosidase assays were performed as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
“…The initiating protease(s) has not yet been identified. Recently it was shown that an adaptor protein, Ppr1, binds to both RsmA and the substrate binding domain of Rip1 and prevents signal-independent degradation of RsmA (Figure 4c) [60]. The adaptor is proposed to provide specificity to the system by tethering RsmA to the protease.…”
Section: Signal Sensingmentioning
confidence: 99%
“…The adaptor is proposed to provide specificity to the system by tethering RsmA to the protease. This model predicts that additional adaptor proteins exist to connect Rip1 with each of the remaining anti-sigma factors [60]. …”
Section: Signal Sensingmentioning
confidence: 99%
“…The mycobacterial Rip1 protease can degrade anti-sigma factors of σ M , σ K and σ L . Adaptor proteins may help Rip1 achieve specificity in signaling, as suggested by selective tethering of the Rip1 PDZ domain to the anti-sigma factor σ M , but not to the anti-sigma factors σ K and σ L , by the adaptor Ppr1 (Schneider et al, 2013). Allosteric interactions between the adaptor SafA and the PhoQ periplasmic sensor domain specifically link EvgS/EvgA and PhoQ/PhoP signaling in response to acid pH (Eguchi et al, 2012).…”
Section: Signal Discriminationmentioning
confidence: 99%